Vertical Code Completion: Going Beyond the Current Ctrl+Space - Silva Junior, Luiz Laerte Nunes; Oliveira, Thiago Nazareth; Plastino, Alexandre; Murta, Leonardo Gresta Paulino (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2012: Anais do VI Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2012)
In the software development field, the amount ofdata related to documentation and to the source code itselfis huge. Relevant knowledge can be extracted from this data,provided that adequate tools are in place. In this context, datamining can be seen as an important tool. This paper presentsan approach to mine sequential patterns from source code andto suggest these patterns to developers, according to what isbeing coded. As a result, a plugin for the Eclipse IDE, calledVertical Code Completion, was developed and applied over thesource code repository of an academic management system.The obtained patterns were analyzed by the developers ofthis system with different expertise levels and the proposedapproach reached good results, indicating that 71.6% of thesuggestions were relevant.